Pengelolaan Pembelajaran Berbasis Sentra dalam Menstimulasi Perkembangan Sosial-Emosional Anak Usia Dini - Muhammad Muqorrobin; Tri Suminar (Pusat Riset dan Inovasi Nasional, 2025)
This study aims to comprehensively describe the management of center-based learning in stimulating the social-emotional development of early childhood at the Nastiti Siwi Ungaran Timur Daycare Center (TPA). The background of the study is rooted in the pivotal role of the center learning model in fostering children’s social skills, emotional regulation, and ability to engage in collaborative play, as well as the challenges in its implementation that often fail to fully address developmental needs. A qualitative approach was employed using a case study method, with data collected through observations, in-depth interviews, and documentation. The findings reveal that the rotating center model, which has been widely applied, does not adequately support thematic consistency or ensure the continuity of children’s social-emotional growth. Teachers tend to focus primarily on achieving activity targets rather than promoting competencies related to emotional awareness, regulation, and social interaction. As a result, children’s engagement in play often emphasizes task completion rather than meaningful experiences that nurture self-regulation and empathy. To address these challenges, an intervention was carried out in the form of collaborative mentoring. This intervention emphasized three key aspects: (1) formulating explicit social-emotional objectives in lesson planning, (2) designing the learning process flow systematically before, during, and after play activities, and (3) optimizing the environment as a medium of stimulus to encourage responsive interactions. The results demonstrate that responsive center-based learning significantly improves the quality of children’s social interactions, enhances their emotional regulation abilities, and increases their active participation in play. The study concludes that effective management of center-based learning requires not only structured planning but also adaptive practices that respond to children’s emotional and social developmental needs. It is recommended that teachers’ capacity be strengthened through reflective training and ongoing practice mentoring to ensure sustainability, consistency, and the holistic development of early childhood in daycare settings